2021
DOI: 10.1063/5.0024479
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent kinetic energy in 2D isothermal interchange-dominated scrape-off layer E × B drift turbulence: Governing equation and relation to particle transport

Abstract: This paper studies the turbulent kinetic energy (k ⊥ ) in 2D isothermal electrostatic interchange-dominated ExB drift turbulence in the scrape-off layer, and its relation to particle transport. An evolution equation for the former is analytically derived from the underlying turbulence equations. Evaluating this equation shows that the dominant source for the turbulent kinetic energy is due to interchange drive, while the parallel current loss to the sheath constitutes the main sink. Perpendicular transport of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(77 citation statements)
references
References 42 publications
4
73
0
Order By: Relevance
“…In this paper, we adopt recent insights from the development of 𝜅 models based on 2D electrostatic interchange E × B drift turbulence simulations for the scrape-off layer (SOL) [17,24,25] using the TOKAM2D code. [9,27] In Reference [17] it is shown that the anomalous transport due to isothermal electrostatic E × B fluctuations can be described rather accurately through a diffusive model…”
Section: Closure Of the Transport Fluxesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we adopt recent insights from the development of 𝜅 models based on 2D electrostatic interchange E × B drift turbulence simulations for the scrape-off layer (SOL) [17,24,25] using the TOKAM2D code. [9,27] In Reference [17] it is shown that the anomalous transport due to isothermal electrostatic E × B fluctuations can be described rather accurately through a diffusive model…”
Section: Closure Of the Transport Fluxesmentioning
confidence: 99%
“…We also left out the smaller contributions from the viscosity to the perpendicular currents. † The contribution of the diamagnetic current to the right-hand side of this equation can be elaborated as [17,36]…”
Section: Model Equation For 𝜿mentioning
confidence: 99%
See 2 more Smart Citations
“…We adopt the tangent mode of AD for an accurate gradient computation. To keep the parameter set limited, we do not estimate such coefficients directly, but we employ the recently developed 𝜅-model for interchange turbulence, [21] which allows retrieving spatially dependent transport coefficients using fewer modelling parameters. [22] In Section 2, we describe the parameter estimation framework developed, while in Section 3, we give a brief overview of the 𝜅-model equations.…”
Section: Introductionmentioning
confidence: 99%